التفاعل الاجتماعي للشباب الجامعي ودوره في التحصيل الدراسي - شعوبي, فضيلة (جامعة الوادي - University of Eloued, 2023)
تهدف الدراسة الحالية إلى تحديد أنماط التفاعل الاجتماعي للشباب الجامعي ودوره في تحصيلهم الدراسي، وقد استخدمت الباحثة في التحليل المنهج الوصفي اعتماداً على استبيان صُمّم لهذه الغاية يتكون من 22 فقرة ضمن ثلاث محاور، وبغرض الوصول إلى نتائج أكثر دقة وُزّع الاستبيان على عينة عشوائية من طلبة السنة الثالثة ليسانس علم الاجتماع بجامعة الوادي، وتوصلت الباحثة إلى نتائج أهمها أنّ مستوى التفاعل بين كل من الطالب وزملاء الدراسة والطالب مع الأساتذة كان مرتفعا، في حين جاء مستوى التفاعل الاجتماعي للطالب مع إدارة الجامعة متوسطا، وتفسر هذه التفاعلات في مجملها النتائج الايجابية للطلبة والتي جاءت في معظمها جيدة وذلك بما نسبته 40%، وهو ما يشير إلى الدور الفعَّال للتفاعل الاجتماعي في التحصيل الدراسي. Abstract: This study aims to determine the patterns of social interaction of university youth and its role in their academic achievement, The researcher used a descriptive approach in the analysis, based on a questionnaire designed for this purpose, consisting of 22 items within three axes. It was distributed to a random sample of third year students of the Bachelor of Sociology at Eloued University. The most important results are: The interaction between each of the students and classmates and the student with the professors was high, While the level of the student's social interaction with the university administration was average, These interactions explain the positive results of the students, which were mostly good, with a percentage of 40%, This points to the active role of social interaction with academic achievement.
The role of social interaction for university youth in academic achievement
مقال
Keywords: تفاعل اجتماعي ، تحصيل دراسي ، شباب جامعي ، جامعة; Social interaction, academic achievement, university youth, university